Association Between Specific Type 2 Diabetes Therapies and Risk of Alzheimer’s Disease and Related Dementias in Propensity-Score Matched Type 2 Diabetic Patients - Torrandell-Haro, Georgina; Branigan, Gregory L.; Brinton, Roberta Diaz; Rodgers, Kathleen E. (Frontiers in Aging Neuroscience, 2022)
Objective: We sought to determine the impact of Type 2 Diabetes Mellitus (T2D) anti-hyperglycemic medications (A-HgM) on risk of Alzheimer’s disease and related dementias (ADRD) outcomes including vascular dementia, and non-AD dementia such as frontotemporal, Lewy bodies, and mixed etiology dementias. Research Design and Methods: This retrospective cohort study used the US-based Mariner claims dataset. 1,815,032 T2D participants 45 years and older with records 6 months prior and at least 3 years after the diagnosis of T2D were included. Claims were surveyed for a diagnosis of ADRD 12 months post T2D diagnosis. A propensity score approach was used to minimize selection bias. Analyses were conducted between January 1st and February 28th, 2021. Results: In this cohort study A-HgM exposure was associated with decrease in diagnosis of AD (RR, 0.61; 95% CI, 0.59-0.62; p<0.001), vascular dementia (RR, 0.72; 95% CI, 0.69-0.74; p<0.001) and non-AD dementia (RR, 0.67; 95% CI, 0.66-0.68; p<0.001). Metformin was associated with the greatest risk reduction and insulin with the least reduction in risk compared to patients not receiving A-HgM for ADRD risk. However, patients with a diagnosis of AD, while either on metformin or insulin, were older in age and predominately female, than individuals on these drugs that did not develop AD. Mean (SD) follow-up was 6.2 (1.8) years. Conclusions: After controlling for age, sex, and comorbidities, A-HgM in patients with T2D was associated with a reduced risk of ADRD. These findings provide evidence in support of T2D as a risk factor for ADRD and the beneficial impact of early and effective control of hyperglycemia to mitigate risk.